The Effectiveness of Metacognition Strategies Training on Problem-Solving Function in Guidance School Students - Ali Reza Jazayeri (Journal of Rehabilitation, 2003)
Objective: The main purpose of this study is to assign the effect and role of metacognition strategies trainings in problem-solving function. In other word, a comparison among-different educational methods in these skills and assigning the most effective strategy for training metacognition skills.